Effect of Multiwalled Carbon Nanotubes on the Properties of Poly(methyl methacrylate) in PMMA/CNT Nanocomposites. Issue 1 (July 2014) - Tripathi, Sandeep Nath; Singh, Sauraj; Malik, Rajender Singh; Choudhary, Veena; Saiter, Jean‐Marc
Summary In the present paper poly(methyl methacrylate) (PMMA)/multiwall carbon nanotubes (MWCNT) nanocomposites were prepared by bulk polymerization of MMA in presence of varying amounts of MWCNT and 2‐hydroxyethyl methacrylate (HEMA) modified MWCNT (HCNT) using azobisisobutyronitrile (AIBN) as an initiator. The nanocomposites were characterized for their structural, thermal, electrical and morphological behaviour using Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, dynamic mechanical analysis (DMA), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and scanning electron microscopy (SEM). The presence of nanofiller inhibits the formation of head to head linkages as all the nanocomposite samples show two step degradation whereas PMMA prepared under similar condition showed three step degradation. The glass transition temperature (Tg) of PMMA increased after incorporation of MWCNTs. The obtained nanocomposites show an increasing trend in the molecular weight with increase in the wt % of MWCNT whereas it decreases with the increasing initiator concentration. It was observed that the electrical conductivity is the function of molecular weight of the polymer as well as the content of MWCNT in the nanocomposites. The electrical conductivity of PMMA/HCNT composites was slightly lower as compared to PMMA/MWCNT whereas an increasing trend in the storage modulus of PMMA/HCNT nanocomposites was observed.